A test for instrument validity - Toru Kitagawa (Centre for Microdata Methods and Practice (cemmap), 2014)
This paper develops a specification test for instrument validity in the heterogeneous treatment effect model with a binary treatment and a discrete instrument. The strongest testable implication for instrument validity is given by the condition for nonnegativity of point-identifiable complier's outcome densities. Our specification test infers this testable implication using a variance-weighted Kolmogorov-Smirnov test statistic. Implementation of the proposed test does not require smoothing parameters, even though the testable implications involve non-parametric densities. The test can be applied to both discrete and continuous outcome cases, and an extension of the test to settings with conditioning covariates is provided.
Keywords: C12; C15; C21; 330; Treatment Effects; Instrumental Variable; Specification Test; Bootstrap